Semi-fortified Palatial Complexes in Central Asia: New Work at the Great Kyz Kala, Merv, Turkmenistan. Issue 1 (5th December 2018) - Williams, Tim; Campbell, Katie; Jorayev, Gaygysyz; Wordsworth, Paul; Jepbarov, Rejep; Moriset, Sébastien
Abstract : Within Central Asia there is an unusual group of earthen buildings (köshks), usually constructed on raised platforms, with vertical engaged columns forming iconic 'corrugations' on the exterior walls. The complexes are semi-fortified, with a second storey entrance, and often with asymmetrical ranges of rooms around an internal courtyard. Little systematic archaeological work has taken place on these monuments, which have mainly been studied as relatively eroded standing structures. However, recent work at the Great Kyz Kala at Merv, Turkmenistan, the largest surviving monumental köshk in Central Asia, has provided more details of construction and use. The excavations suggest that this complex was constructed in the 8 th /9 th century CE, with well-appointed rooms on the second storey, including a large hall, and functional rooms and storage spaces around a courtyard on the lower floor. The complex was set within an enclosure, containing gardens and possibly ancillary buildings. This particular köshk may have acted as an elite palatial suburban residence, perhaps for the governor of Merv.